Small Volume Biopsy in Pediatric Tumors An Atlas for Diagnostic Pathology (Springer International Publishing, 2018)
This richly illustrated book will help presurgically diagnose pediatric/young adult tumors. The content is divided into two parts. The first part shows step-by-step how to perform a small volume specimen such as fine needle aspiration/core needle biopsy and how to correlate the morphology with the clinical, radiological, and/or molecular information. In turn, the second part presents a comprehensive overview of the various tumor entities. The content represents diagnostic modalities from the major diagnostic centers worldwide, and is supplemented by the authors` 25 years of experience in diagnosing pediatric tumors. This book will successfully guide practitioners, researchers and oncology pediatricians through the process of sample harvesting and diagnosing. Pediatric tumors represent a large variety of lesions including pseudotumors of inflammatory and non-inflammatory origin, various types of lympadenopathy, benign lesions, specific sarcomas, and blastemal malignancies. These age-specific and histotype-specific tumors of various origin, evolution and prognosis are often characteristic in morphological and molecular levels, making their diagnosis highly specialized.